Gemcitabine and taxanes in metastatic breast cancer: a systematic review - Gudena, Vinay (Dove Medical Press, 2008)
Incremental advances over the last two decades in the treatment of stage IV metastatic breast cancer (MBC) have resulted in significantly prolonging the average life expectancy. In 2008, the estimated 5-year relative survival rate for MBC is 27% which compares favorably to rates in stage IV lung (3%) and pancreatic cancers (1%). Despite these advances, MBC remains an incurable disease, often associated with many symptoms and a decreased quality of life (QoL). Therefore, therapy goals in the treatment of MBC include prolonging both progression-free survival and overall survival rates, while at the same time improving QoL by palliation of symptoms. Therefore, systemic chemotherapy ideally should not induce unnecessary toxicities. Once chemotherapy is indicated, a number of drugs and regimens are available but only a few offer both palliation of symptoms (responses to therapy) and overall survival benefit. The addition of novel biologic compounds to chemotherapy has been shown in phase III trials to improve all the above mentioned clinical outcomes in MBC. This review will discuss data supporting the use of gemcitabine/taxane combinations in the treatment of MBC.